The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c5fo01401h
|View full text |Cite
|
Sign up to set email alerts
|

Formation of malondialdehyde (MDA), 4-hydroxy-2-hexenal (HHE) and 4-hydroxy-2-nonenal (HNE) in fish and fish oil during dynamic gastrointestinal in vitro digestion

Abstract: Marine lipids contain a high proportion of polyunsaturated fatty acids (PUFA), including the characteristic long chain (LC) n-3 PUFA. Upon peroxidation these lipids generate reactive products, such as malondialdehyde (MDA), 4-hydroxy-2-hexenal (HHE) and 4-hydroxy-2-nonenal (HNE), which can form covalent adducts with biomolecules and thus are regarded as genotoxic and cytotoxic. PUFA peroxidation can occur both before and after ingestion. The aim of this study was to determine what levels of MDA, HHE and HNE ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 54 publications
3
35
0
Order By: Relevance
“…Indeed, highly significant and strong correlations were found among 4‐HHE, PROP, and TBARS in digests, and LC n‐3 PUFAs in muscle foods (all r between 0.838 and 0.975, all p < 0.001), but not with ALA, the most dominantly present n‐3 PUFA in mammal and poultry muscles ( Table ). Previous studies also reported the formation of 4‐HHE and MDA during the digestion of herring, salmon, and various fish oils, accompanied by relatively low 4‐HNE formation . In agreement to our results, Steppeler et al .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, highly significant and strong correlations were found among 4‐HHE, PROP, and TBARS in digests, and LC n‐3 PUFAs in muscle foods (all r between 0.838 and 0.975, all p < 0.001), but not with ALA, the most dominantly present n‐3 PUFA in mammal and poultry muscles ( Table ). Previous studies also reported the formation of 4‐HHE and MDA during the digestion of herring, salmon, and various fish oils, accompanied by relatively low 4‐HNE formation . In agreement to our results, Steppeler et al .…”
Section: Resultssupporting
confidence: 93%
“…Muscle foods from different animal origin vary widely in concentrations of heme‐Fe, n‐3 , and n‐6 PUFAs, and endogenous antioxidants such as vitamin E, carnosine, and anserine, all compounds with the ability to influence oxidative reactions during digestion. Yet, the variation in the sensitivity to oxidation during digestion of muscles originating from various animal species is only scarcely explored . Muscle foods are classified according to their mammal, avian, or aquatic origin, or as “white meat” or “red meat,” referring to their low and high heme‐Fe contents, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the higher PUFA contents of vegetable oil, the greater MDA‐generating potential it may exhibit. Previous literature reported that aldehydes derived from the oxidative decomposition of PUFA hydroperoxides (Larsson et al ., ). So LO, containing the highest amount of PUFA, showed the greatest MDA‐generating ability, which also explained why MDA content of LO was the highest in our experiment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only in the last few years have some research groups started to bridge this gap by investigating the levels of reactive aldehydes and epoxidation products during oil digestion …”
Section: Bridging the Gap Between Spoilage And Health Implicationsmentioning
confidence: 99%